Risk stratification of symptomatic patients suspected of colorectal cancer using faecal and urinary markers. (17th October 2018) - Widlak, M. M.; Neal, M.; Daulton, E.; Thomas, C. L.; Tomkins, C.; Singh, B.; Harmston, C.; Wicaksono, A.; Evans, C.; Smith, S.; Savage, R. S.; Covington, J. A.; et al.
Abstract: Aim: Faecal markers, such as the faecal immunochemical test for haemoglobin (FIT) and faecal calprotectin (FCP), have been increasingly used to exclude colorectal cancer (CRC) and colonic inflammation. However, in those with lower gastrointestinal symptoms there are considerable numbers who have cancer but have a negative FIT test (i.e. false negative), which has impeded its use in clinical practice. We undertook a study of diagnostic accuracy CRC using FIT, FCP and urinary volatile organic compounds (VOCs) in patients with lower gastrointestinal symptoms. Method: One thousand and sixteen symptomatic patients with suspected CRC referred by family physicians were recruited prospectively in accordance with national referring protocol. A total of 562 patients who completed colonic investigations, in addition to providing stool for FIT and FCP as well as urine samples for urinary VOC measurements, were included in the final outcome measures. Results: The sensitivity and specificity for CRC using FIT was 0.80 [95% confidence interval (CI) 0.66–0.93] and 0.93 (CI 0.91–0.95), respectively. For urinary VOCs, the sensitivity and specificity for CRC was 0.63 (CI 0.46–0.79) and 0.63 (CI 0.59–0.67), respectively. However, for those who were FIT‐negative CRC (i.e. false negatives), the addition of urinary VOCs resulted in a sensitivity of 0.97 (CI 0.90–1.0) and specificity of 0.72 (CI 0.68–0.76). Conclusions: When applied to the FIT‐negative group, urinary VOCs improve CRC detection (sensitivity rises from 0.80 to 0.97), thus showing promise as a second‐stage test to complement FIT in the detection of CRC.